2020
DOI: 10.1371/journal.pone.0239228
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of daily intermittent or continuous short-arm centrifugation during 60-day 6o head down bed rest (AGBRESA study)

Abstract: Artificial gravity through short-arm centrifugation has potential as a multi-system countermeasure for deconditioning and cranial fluid shifts that may underlie ocular issues in microgravity. However, the optimal short-arm centrifugation protocol that is effective whilst remaining tolerable has yet to be determined. Given that exposure to centrifugation is associated with presyncope and syncope and in addition motion sickness an intermittent protocol has been suggested to be more tolerable. Therefore, we asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 34 publications
1
43
0
1
Order By: Relevance
“…Twenty‐four subjects participated in this study, which was conducted at the :envihab facility at the German Aerospace Center (DLR) in Cologne, Germany (Frett et al, 2020 ). Subjects were recruited by the DLR and eligibility for enrollment was determined according to the International Academy of Astronautics’ guidelines for bed rest studies (Sundblad et al, 2014 ), including a clinical eye examination that confirmed the absence of ocular disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐four subjects participated in this study, which was conducted at the :envihab facility at the German Aerospace Center (DLR) in Cologne, Germany (Frett et al, 2020 ). Subjects were recruited by the DLR and eligibility for enrollment was determined according to the International Academy of Astronautics’ guidelines for bed rest studies (Sundblad et al, 2014 ), including a clinical eye examination that confirmed the absence of ocular disease.…”
Section: Methodsmentioning
confidence: 99%
“…The iAG exposure consisted of 6 periods of AG that lasted 5 min each, with a 3‐min break between each period. The centrifuge arm radius and velocity were adjusted according to each subject's height to achieve 1 g at the center of mass (approximately 2 g at the feet and 0.3 g at the eyes) (Frett et al, 2020 ). All centrifugation sessions were performed in the 0° supine posture, and on testing days, ocular measures were acquired from the cAG and iAG subjects before the centrifugation session.…”
Section: Methodsmentioning
confidence: 99%
“…More detailed information is set forth in Guidelines for standardisation of bed rest studies in the spaceflight context (Sundblad & Orlov, 2014). Details of the AGBRESA study have been published which specify the daily routines (Frett et al., 2020).…”
Section: Methodsmentioning
confidence: 99%
“…AG was produced by rotating the participants on a centrifuge arm with a 3.0-m radius. The rotational speed of the centrifuge was calculated individually based upon each participant's anthropometry to produce 1Gz at the center of mass (22). Participants' cardiorespiratory parameters were continuously monitored by trained medical personnel.…”
Section: Artificial Gravitymentioning
confidence: 99%